The Soviet High Command, 1967-1989 : Personalities and Politics. - Herspring, Dale R. (Dale Roy) (Princeton : Princeton University Press, 2014)
The recent transformations in the USSR are nowhere more evident than in the Soviet military. Top-level military officers have been relieved of their positions, Gorbachev has warned of lean times for the military, the symbolic role of the armed forces has been downgraded, and the concept of ""military sufficiency"" points to major modifications in Soviet force structure. Contrary to some who see Gorbachev as a Sir Galahad out to slay the evil military high command, Dale Herspring concludes that the relationship between the highest Soviet political and military leaders is at the moment more s
Cover; Contents; Acknowledgments; Part I The Setting; Part II The Grechko Era, 1967-1976; Part III The Ogarkov Era, 1977-1984; Part IV The Akhromeyev Era, 1984-1988; Part V Looking to the Future.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Generals -- Soviet Union; Soviet Union -- Armed Forces -- History; Soviet Union -- Politics and government -- 1945-1991.; Généraux -- URSS; URSS -- Politique et gouvernement -- 1945-1991.; HISTORY -- Military -- General; POLITICAL SCIENCE -- Political Process -- Political Advocacy; Armed Forces; Generals; Politics and government; Soviet Union; 1945-1991; History